Prenatal assessment of Tetralogy of Fallot: A multicenter prospective cohort study. (March 2021) - Fruitman, Deborah S.; Bloomfield, Valerie; Mueller, Brigitte; Kwok, Hilary; Manlhiot, Cedric; Nield, Lynne E.
Abstract: Predicting clinical outcomes in prenatally diagnosed Tetralogy of Fallot remains a challenge. This multicenter study aimed to prospectively evaluate fetal echocardiographic parameters associated with early neonatal intervention (<60 days). Secondary outcomes included oxygen saturation <80% at delivery, prostaglandin need, and valve sparing vs transannular patch repair. Serial fetal echocardiographic measurements were obtained. Patients were followed through pregnancy until 12 months post-surgical correction. Stepwise selection of variables was performed to identify important associated risk factors. Binomial logistic regression was used to analyze the primary and secondary outcomes. Between 2009 and 2014, N = 54/79 were recruited at 24 weeks gestational age (range 21–29 weeks), 2 died in utero and 3 died postnatally. The pulmonary valve z-score was smaller in patients who underwent early intervention (−3.4 ± 1.1 vs. −2.5 ± 1.8; p = .044) and smaller pulmonary valve z score was associated with transannular patch (Odd ratio (OR) 1.9; CI 1.2–3.1; p = .008). Reversal of flow in the ductus arteriosus was associated with early intervention (OR 6.6; CI 1.4–38.3; p = .023). Patients with an underlying genetic syndrome were more likely to undergo early intervention (11/15 (73%) vs 7/36 (23%), p = .001). In conclusion, for this prospective cohort, reversed flow in the ductus arteriosus was the only factor significantly associated with early intervention with a lower pulmonary valve z-score being associated with transannular patch repair. Patients with a genetic syndrome were more likely to undergo an early intervention. Highlights: Predicting early outcomes in prenatally diagnosed tetralogy of Fallot remains a challenge. Reversal in ductus arteriosus flow is associated with early intervention. Lower pulmonary valve z-score is associated with a transannular patch repair. Syndromic patients were more likely to undergo an early intervention.